2020
DOI: 10.1016/j.jjcc.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Integrated diagnostic approach to wild-type transthyretin cardiac amyloidosis with the use of high-sensitivity cardiac troponin T measurement and 99mTc-pyrophosphate scintigraphy

Abstract: Background: The diagnosis of wild-type transthyretin cardiac amyloidosis (ATTRwt) is frequently missed or delayed because of the limited specificity of manifestations. We investigated the utility of combined assessment of high-sensitivity cardiac troponin T (hs-cTnT) measurement and 99m Tc-pyrophosphate ( 99m Tc-PYP) scintigraphy as diagnostic modalities in ATTRwt. Methods: We divided 39 consecutive ATTRwt patients into two groups depending on whether serum hs-cTnT measurement and 99m Tc-PYP scintigraphy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…And the cohort study conducted in Spain indicated that in 108 cases diagnosed with ATTRwt using PYP scintigraphy (including cases not undergoing biopsy), about 20% were unexpectedly women, low voltage in limb leads in ECG was less frequent (22%), not only concentric LVH but also asymmetric hypertrophy existed to some extent (23.1%), and there were also many patients with heart failure with reduced ejection fraction with decreased left ventricular contractility among ATTR-CM patients with heart failure (left ventricular ejection fraction <50%: 36.8%) [9]. Thus, in response to the current global progress in which the diversity of clinical features in ATTR-wt is being elucidated by new effective diagnostic methods, Ochi et al demonstrate novel findings for the diversity of this disease in Japan through the present study [10]. They compared two groups before and after using a protocol to diagnose with 99mTc-PYP scintigraphy and high-sensitivity cardiac troponin T, a representative high-sensitive marker of myocardial injury.…”
supporting
confidence: 56%
“…And the cohort study conducted in Spain indicated that in 108 cases diagnosed with ATTRwt using PYP scintigraphy (including cases not undergoing biopsy), about 20% were unexpectedly women, low voltage in limb leads in ECG was less frequent (22%), not only concentric LVH but also asymmetric hypertrophy existed to some extent (23.1%), and there were also many patients with heart failure with reduced ejection fraction with decreased left ventricular contractility among ATTR-CM patients with heart failure (left ventricular ejection fraction <50%: 36.8%) [9]. Thus, in response to the current global progress in which the diversity of clinical features in ATTR-wt is being elucidated by new effective diagnostic methods, Ochi et al demonstrate novel findings for the diversity of this disease in Japan through the present study [10]. They compared two groups before and after using a protocol to diagnose with 99mTc-PYP scintigraphy and high-sensitivity cardiac troponin T, a representative high-sensitive marker of myocardial injury.…”
supporting
confidence: 56%
“…Twelve studies collected data in North America [ 18 29 ], three in Asia [ 30 32 ], six in Europe [ 3 , 33 – 37 ], and two were conducted internationally [ 38 , 39 ]. Fourteen publications reported data for ATTRwt-CM [ 40 ], eleven for ATTRv-CM [ 3 , 18 , 21 , 22 , 24 – 26 , 29 , 30 , 33 , 39 ] and seven for mixed ATTR-CM populations (ATTRwt-CM and ATTRv-CM [ 18 , 19 , 23 , 24 , 27 , 28 , 37 ]).…”
Section: Resultsmentioning
confidence: 99%
“…There are no studies specifically addressing the diagnostic performance of hs‐troponins in ATTR amyloidosis. Nonetheless, the apparent prevalence of this condition has increased steadily since the introduction of hs‐TnT measurement and 99m Tc‐pyrophosphate scintigraphy in patients with clinical suspicion of ATTRwt 79 …”
Section: Biomarkers Of Cardiac Involvementmentioning
confidence: 99%